Impact of investments in training and advertising on the market value relevance of a company's intangibles: The effect of the economic crisis in Spain - Lidia García-Zambrano; Arturo Rodríguez-Castellanos; Jose Domingo García-Merino (European Research on Management and Business Economics (ERMBE), 2018)
This paper seeks to analyze the influence investment in that investment in intangible resources, specifically training and advertising, has on the corporate market value. A sample of the main Spanish companies, those quoted on the IBEX-35, revealed that both investing in training and in advertising separately have a positive relationship with the Market/Book ratio a year ahead (in both periods analyzed, 2006–2009 and 2008–2011). Regarding the joint effect, a positive and significant impact is also seen in both periods. The results are even more relevant for the second period (2008–2011) and we could therefore check how investments made during the current period of crisis have had a higher impact on market value. The relevance of our paper for academics and practitioners should be noted, as there were no previous similar studies in Spain relating investments in these types of intangibles and market value using IBEX-35 companies. Practitioners likewise need to consider the positive effect on competitiveness of investment in competencies (human and relational competencies).
Keywords: M1; O34; 650; Intellectual Capital; Investment in training; Investment in advertising; Depreciation; Business value